2017
DOI: 10.1002/itl2.16
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Vehicles: Enabling safe, secure, and private vehicular crowdsourcing

Abstract: Safely avoiding accident prone routes is vital to maintain safe and intelligent transportation. Real‐time crowd sourcing of accident causing factors (eg, icy roads, rain slicked road patches) combined with historical accident information can be utilized by intelligent navigation systems to avoid accident prone routes. A vehicle cloud can compute such safe routes and react faster than a centralized service given crowdsourced data such as images, sensor readings, and so on. However, in addition to the intelligen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In [18], the paper discusses security and privacy using the following: -Authenticated crowd sourced data: The software controlling the vehicle is prone to malicious attacks misleading/forcing the vehicle to take a different/desired route. These spoofed messages should be detected and separated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [18], the paper discusses security and privacy using the following: -Authenticated crowd sourced data: The software controlling the vehicle is prone to malicious attacks misleading/forcing the vehicle to take a different/desired route. These spoofed messages should be detected and separated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In view of the aggregation functionality of the cluster head, the authors showed the need for such a micro cloud. From the security and privacy standpoint, Joy et al in [4] discussed various security and privacy challenges for IoV. They also presented different approaches like crowdsourced authentication and haystack privacy for ensuring safe and secure communication in IoV.…”
Section: B Recent Advances In Iovmentioning
confidence: 99%
“…In other words, besides the official rules, there is a set of informal rules that control traffic. From a systemic point of view, it is immediately obvious that observance of informal rules, communication between road users, and behavioral prediction of drivers are important to support the flow of traffic and to minimize the number of accidents on the road [4].…”
Section: Introductionmentioning
confidence: 99%
“…The sending vehicle or an intermediate vehicle in a junction looks for the position of the neighbouring junctions using the map. A score is given to each junction considering the traffic density and the curvemetric distance to the destination [Joy, Rabsatt and Gerla (2018)]. The best destination junction (the junction with the highest score) is the geographically closest junction to the destination vehicle having the highest vehicular traffic.…”
Section: Recovery Strategymentioning
confidence: 99%